2020
DOI: 10.1186/s13063-020-4154-1
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter randomized trial of personalized acupuncture, fixed acupuncture, letrozole, and placebo letrozole on live birth in infertile women with polycystic ovary syndrome

Abstract: Background: Traditional Chinese medicine (TCM) usually involves syndrome differentiation and treatment. Acupuncture, one form of TCM, requires the selection of appropriate acupoints and needling techniques, but many clinical trials on acupuncture have used fixed acupuncture protocols without accounting for individual patient differences. We have designed a multicenter randomized controlled trial (RCT) to evaluate whether personalized or fixed acupuncture increases the likelihood of live births in infertile wom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…(2) Other post-HSG fertility-enhancing treatments (such as ovulation stimulation and traditional Chinese medicine) might also affect the spontaneous pregnancy rate. Therefore, the influence of spontaneous pregnancy rate by oil-based contrast agents was attenuated (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Other post-HSG fertility-enhancing treatments (such as ovulation stimulation and traditional Chinese medicine) might also affect the spontaneous pregnancy rate. Therefore, the influence of spontaneous pregnancy rate by oil-based contrast agents was attenuated (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…And the keyword “low-frequency electroacupuncture,” which existed from 2013 to 2014 with the strength of citation burst of 3.88, indicates that low-frequency electroacupuncture is the most commonly applied acupuncture therapy in the treatment of PCOS. Furthermore, more relevant randomized controlled trials have been conducted to evaluate the effects of acupuncture on improving the quality of life, ovulation rates, and insulin resistance of PCOS patients [ 22 , 45 , 46 ]. Regrettably, there is a lack of convincing evidence for the efficacy of acupuncture in treating women with PCOS [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang S et al. found that personalized acupuncture can improve live birth rates (LBRs) in infertile women with PCOS in a multicenter RCT ( 28 ). However, in 2017 and 2018, the Journal of American Medical Association published two trial reports examining the potential effect of acupuncture on improving in vitro fertilization (IVF) or LBR in women with PCOS.…”
Section: Treatment Of Pcos In Tcmmentioning
confidence: 99%